Characterization and comparison of cold brew and cold drip coffee extraction methods. (6th August 2018) - Angeloni, Giulia; Guerrini, Lorenzo; Masella, Piernicola; Innocenti, Marzia; Bellumori, Maria; Parenti, Alessandro
Abstract: BACKGROUND: Each region of the world has its own methods, protocols, instruments and procedures regarding how to brew coffee. The final result in the cup is strongly affected by the extraction method, and many studies have focused on this subject. However, few studies have investigated slow, cold extraction methods, despite their popularity among baristas. Therefore, the present study aimed to characterize and compare two cold extraction methods: cold brew and cold drip. RESULTS: Physical and chemical analyses were used to describe coffee beverages in terms of pH, total solids, refractive index, density and viscosity. Caffeine and cinnamic acids were quantified using high‐performance liquid chromatography (HPLC)/diode array detector and HPLC/mass spectrometry. A sensory evaluation included aroma, flavor and textural attributes. CONCLUSIONS: Significant differences were found in the chemical and physical parameters, both between and within the two methods, as a function of the extraction temperature and contact time. Similarly, the sensory evaluation found differences in flavor profiles, as measured in terms of bitterness, sweetness, sourness and global intensity. © 2018 Society of Chemical Industry